2011
DOI: 10.2478/s13380-011-0002-9
|View full text |Cite
|
Sign up to set email alerts
|

Voltage-gated calcium channels are not affected by the novel anti-epileptic drug lacosamide

Abstract: The novel anti-epileptic drug lacosamide targets two proteins – voltage-gated sodium channels and collapsin response mediator protein 2 (CRMP-2) – suggesting dual modes of action for lacosamide. We recently identified the neurite outgrowth and axonal guidance protein CRMP-2 as a novel partner and regulator of the presynaptic N-type voltage-gated Ca2+ channel (CaV2.2) [Brittain et al., J. Biol. Chem. 284: 31375–31390 (2009)]. Here we examined the effects of lacosamide on voltage-gated Ba2+ channels. Lacosamide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 55 publications
1
17
0
Order By: Relevance
“…We have previously shown that (R)-LCM does not inhibit Ca 2+ currents in hippocampal neurons [70] but whether ( S )-LCM inhibits Ca 2+ currents in sensory neurons is unknown. For these voltage-clamp experiments we chose a concentration of 10µM ( S )-LCM, a value ~8 times the IC 50 value calculated from Ca 2+ imaging experiments, to assess potential off-target effects.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously shown that (R)-LCM does not inhibit Ca 2+ currents in hippocampal neurons [70] but whether ( S )-LCM inhibits Ca 2+ currents in sensory neurons is unknown. For these voltage-clamp experiments we chose a concentration of 10µM ( S )-LCM, a value ~8 times the IC 50 value calculated from Ca 2+ imaging experiments, to assess potential off-target effects.…”
Section: Resultsmentioning
confidence: 99%
“…Vimpat modulates slow inactivation of Na + channels [22; 56] with an IC 50 of 80 µM [71]. Critically, we and others have demonstrated that at doses active in vivo for inhibition of seizures, ( R )-LCM does not modulate Ca 2+ activity [70]. …”
Section: Introductionmentioning
confidence: 99%
“…Primary cultured hippocampal neurons were treated with 300 μM lacosamide for 0.5–24 hours. Whole cell patch clamp recordings revealed that neither acute nor chronic treatment altered current density or kinetics of activation or inactivation [46]. As the L-type calcium channel currents were inhibited by the presence of nifedipine, currents predominantly represented calcium carried through N-type channels, with a small percentage attributed to P/Q-type channels at this age in culture [47].…”
Section: Does Lacosamide Have a Dual Mode Of Action?mentioning
confidence: 99%
“…Catecholamine A-differentiated (CAD) Cell Culture-CAD cells were cultured exactly as described (20,21).…”
Section: Methodsmentioning
confidence: 99%